Studi Deskriptif Resistensi Individu Terhadap Perubahan Peraturan di Kantor Pelayanan Pajak Pratama Candisari Semarang (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
According to the Financial Minister Decree No. 132/PMK.01/2006 Organization and Work Order of Vertical Instance of Tax General Directorate, the Semarang Pratama Tax Service Office had changed. Despite of the universal and inevitable nature of a change, it rarely took place smoothly, readily and proportionately. A resistance toward a change was a behavioral or emotional respond to the real work or desired change. The sample at this research were 50 employees of Semarang Pratama Tax Service Office of Candisari. The instrument used was psychology scale. For the validity test, the writer employed the formula of product moment correlation. Meanwhile, for the reliability test, used the Alpha Cronbach technique. The data were analyzed, used descriptive statistics. The overall data was processed using the assistance of program computer of SPSS version 12.0 for Windows. The resistance rate of the employees of the office experienced was bipolarization. The research, result shows that the logical resistance rate was of 40%, sociological of 38%, and psychological of 24% on the highest criteria. It suggested that in general, the reaction or attitude displayed by the employees tended to be based on the logical or rational aspect in facing the change. And it was caused by the lack of information and knowledge about the change. Based on the research result, it was proposed for the Semarang Pratama Tax Service Office of Candisari to socialize further more to its employees the whole information about Pratama Tax Service Office, since the unwillingness to support the regulation change of Pratama Tax Service Ojfice was due to the lack of understanding of it wholly in most of them.